2016
DOI: 10.1007/s10143-016-0708-9
|View full text |Cite
|
Sign up to set email alerts
|

The value of lateral spread response monitoring in predicting the clinical outcome after microvascular decompression in hemifacial spasm: a prospective study on 100 patients

Abstract: Microvascular decompression represents an effective treatment for hemifacial spasm. The use of lateral spread response (LSR) monitoring remains a useful intraoperative tool to ensure adequate decompression of the facial nerve. The aim of this study was to assess the value of LSRs intraoperative monitoring as a prognostic indicator for the outcome of microvascular decompression in hemifacial spasm. Our study included 100 patients prospectively. The patients were classified into four groups whether LSRs were tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Some studies have found that intraoperative LSR does not correlate with postdecompression outcome in HFS. 6,24,38 Other studies have reported that intraoperative LSR accurately predicts clinical outcome. 19 A meta-analysis showed that if the LSR is abolished intraoperatively, the success rate of achieving symptom relief will be 90.5% but will drop to 61% when the LSR cannot be abolished intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that intraoperative LSR does not correlate with postdecompression outcome in HFS. 6,24,38 Other studies have reported that intraoperative LSR accurately predicts clinical outcome. 19 A meta-analysis showed that if the LSR is abolished intraoperatively, the success rate of achieving symptom relief will be 90.5% but will drop to 61% when the LSR cannot be abolished intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of movement cannot be reproduced in persons without the condition (e14). The diagnosis of hemifacial spasm can generally be made immediately on inspection, but it can also be confirmed electrophysiologically by the demonstration of pathological lateral spreading of activation (24). A source of additional distress to persons with this condition is that the facial spasms are often wrongly thought to be psychogenic (e15).…”
Section: Hemifacial Spasmmentioning
confidence: 99%
“…18,33 No intraoperative monitoring of the facial nerve was used in our study, as it makes surgery more difficult and limits its reliability. 19,34 The signal characterizing the spasm may indeed disappear while HFS persists when the patient wakes up. 35 Otherwise, monitoring increases morbidity by unnecessary surgical procedures.…”
Section: Discussionmentioning
confidence: 99%